2011
DOI: 10.1007/s11249-011-9780-z
|View full text |Cite
|
Sign up to set email alerts
|

Tribological Properties of Vegetable Oils Modified by Reaction with Butanethiol

Abstract: Corn, canola, and castor-lauric estolide oils were chemically modified by photochemical direct reaction of butanethiol with the double bonds on the hydrocarbon chains. The effect of chemical modifications on viscosity, viscosity index (VI), pour point (PP), cloud point (CP), oxidation stability (RPVOT), 4-ball anti-wear (AW), and extreme pressure (EP) were investigated. The sulfide modified (SM) corn and canola oils showed increased viscosity, increased RPVOT time (more than one order of magnitude), reduced PP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(29 citation statements)
references
References 55 publications
0
28
0
1
Order By: Relevance
“…Thioether hydroxy vegetable oil was synthesized using a chemical reaction of epoxidized vegetable oil and common thiols (92) (Figure 9).…”
Section: Other Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thioether hydroxy vegetable oil was synthesized using a chemical reaction of epoxidized vegetable oil and common thiols (92) (Figure 9).…”
Section: Other Methodsmentioning
confidence: 99%
“…Chemical modification of vegetable oils (corn, canola, and castor-lauric estolide oils) by reaction with butanethiol was reported by Biresaw et al (92). Moreover, the effect of chemical modifications on viscosity, viscosity index, pour point, cloud point, oxidation stability, four-ball antiwear, and extreme pressure was also analyzed.…”
Section: Chemical Thermal and Structural Modificationmentioning
confidence: 97%
“…Por acción de la luz, la temperatura y el oxígeno, estos sitios activos son muy susceptibles al ataque de radicales, y forman compuestos oxigenados polares que resultan en depósitos insolubles y en el aumento de la acidez, la corrosión, la viscosidad y la volatilidad del aceite (Bart et al, 2013;Sharma et al, 2007). Sin embargo, el mejoramiento de las propiedades térmicas y lubricantes de los aceites vegetales se puede lograr mediante modificaciones químicas tales como epoxidación, transesterificación o hidrogenación selectiva (Biresaw et al, 2011;Alves et al, 2013) y el uso de aditivos de tipo antioxidante, detergente, dispersante, de extrema presión o anti-desgaste (Guala et al, 2009;Sharma et al, 2007;Minami et al, 1998).…”
Section: Introductionunclassified
“…17 Thus, some studies were focused on the tribological properties of vegetable oils and the modification for improving their chemical stability. 18,19 A previous study investigated the effect of MoS 2 morphology on the tribological properties of rapeseed oil. 20 The results showed that the MoS 2 nanoplatelets remarkably increase the wear of friction pairs in rapeseed oil.…”
Section: Introductionmentioning
confidence: 99%
“…The chemical composition affects the tribological properties of vegetable oils. 19 The present study investigated the lubricating performance of MoS 2 with different morphologies (hollow nanospheres, nanoplatelets, and microplatelets) in soybean oil (SO). MoS 2 hollow nanospheres remarkably improved the lubricating performance of SO at 1?0 wt-% and revealed potential applications in SO.…”
Section: Introductionmentioning
confidence: 99%